2022
DOI: 10.1186/s43093-022-00158-0
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Continued Usage Intention of Digital Wallets: The Moderating Role of Perceived Technological Innovativeness

Abstract: The paper examines the constructs that instigate the users to adopt digital wallets and continued usage behavior in a developing country perspective, Bangladesh. The researcher used a cross-sectional design to collect the primary data using a self-administered questionnaire. The population consisted of the youth, precisely 18–35, who are tech-savvy and knowledgeable about new technology. The study followed the nonprobability purposive sampling technique, and 330 responses were collected through a structured qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 87 publications
2
12
0
6
Order By: Relevance
“…This study found that PIIT had a significant positive effect on the behavioral intentions of elderly adults to use wearable devices because elderly adults who possess a sense of innovation and self-directed learning toward new technologies generate a sense of pleasure when using wearable devices ( 65 ). This result was confirmed by Shetu et al ( 66 ). They found that people with high PIIT levels tend to develop more positive attitudes toward new information technology and use it more quickly.…”
Section: Discussionsupporting
confidence: 80%
“…This study found that PIIT had a significant positive effect on the behavioral intentions of elderly adults to use wearable devices because elderly adults who possess a sense of innovation and self-directed learning toward new technologies generate a sense of pleasure when using wearable devices ( 65 ). This result was confirmed by Shetu et al ( 66 ). They found that people with high PIIT levels tend to develop more positive attitudes toward new information technology and use it more quickly.…”
Section: Discussionsupporting
confidence: 80%
“…The questionnaire is based on the one developed by Shetu et al (e.g., “ I am currently using the VR exhibit and will continue to use it”) [ 64 ]. The options in the questionnaire ranged from strongly disagree (1) to strongly agree (5).…”
Section: Methodsmentioning
confidence: 99%
“… Continued usage intention CUI1 I am currently using the VR exhibit and will continue to use it. [ 64 ] CUI2 I hope to use VR exhibitions to visit often in the future. CUI3 I would recommend the VR exhibition to those around me.…”
Section: Table A1mentioning
confidence: 99%
“…Personal innovativeness influences the adoption of mobile payment (Li ebana-Cabanillas et al, 2021), wireless internet technology (Lu et al, 2005), mobile commerce (Lu, 2014), ERP (Hwang, 2014) and e-learning systems (Wang and Lin, 2021). Lu (2014) has found the positive influence of personal innovativeness for the continued use of mobile commerce, whereas Shetu et al (2022) found no influence on adoption of digital wallets. Gupta, (2021) found that the Big Five personality traits of an individual determine their innovativeness that positively impacted the completion intention.…”
Section: Personal Innovativenessmentioning
confidence: 99%